The complete chloroplast genome of Soroseris umbrella (Asteraceae) - Lv, Zhen-Yu (Mitochondrial DNA B Resour, 2020)
Soroseris umbrella is an alpine medical plant that is distributed in the alpine screes of China, Bhutan, and India. Here, we identified the complete chloroplast genome of S. umbrella. The complete genome size is 152,462 bp, which consists of a large single-copy (LSC) region of 84,125 bp, a small single-copy (SSC) region of 18,561 bp, a pair of inverted repeat (IR) regions of 24,888 bp each. The overall GC content of genome is 37.7%. A total of 114 unique genes were identified, including 80 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. The phylogenetic analysis based on whole chloroplast genome result shows that S. umbrella is most closely related to Taraxacum.